Extraordinarily Stretchable All‐Carbon Collaborative Nanoarchitectures for Epidermal Sensors. Issue 31 (16th June 2017) - Cai, Yichen; Shen, Jie; Dai, Ziyang; Zang, Xiaoxian; Dong, Qiuchun; Guan, Guofeng; Li, Lain‐Jong; Huang, Wei; Dong, Xiaochen
Abstract : Multifunctional microelectronic components featuring large stretchability, high sensitivity, high signal‐to‐noise ratio (SNR), and broad sensing range have attracted a huge surge of interest with the fast developing epidermal electronic systems. Here, the epidermal sensors based on all‐carbon collaborative percolation network are demonstrated, which consist 3D graphene foam and carbon nanotubes (CNTs) obtained by two‐step chemical vapor deposition processes. The nanoscaled CNT networks largely enhance the stretchability and SNR of the 3D microarchitectural graphene foams, endowing the strain sensor with a gauge factor as high as 35, a wide reliable sensing range up to 85%, and excellent cyclic stability (>5000 cycles). The flexible and reversible strain sensor can be easily mounted on human skin as a wearable electronic device for real‐time and high accuracy detecting of electrophysiological stimuli and even for acoustic vibration recognition. The rationally designed all‐carbon nanoarchitectures are scalable, low cost, and promising in practical applications requiring extraordinary stretchability and ultrahigh SNRs. Abstract : A rational all‐carbon collaborative network for constructing epidermal sensors with significantly improved strain distribution and conductive nanochannels is designed based on collaborative networks of carbon nanotubes and graphene hollow backbones. With the structural and compositional advantages, extraordinary stretchability and sensitivity for real‐time and high accuracy detecting of electrophysiological stimuli of humans and even for acoustic vibration recognition are achieved.